Zakat Payment Antecedents via Digital Platform - Wulandari, Nur Aini; Khoiri, Fatwa Adhma; Rafikasari, Elok Fitriani; Chotimah, Chusnul; Huda, Qomarul (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
This study investigates the factors influencing zakat payment via digital platforms, focusing on platform innovation and transparency as the primary variables, and it employs the Technology Acceptance Model (TAM) as the theoretical framework to examine their impact. A quantitative methodology is adopted using an online survey, and the research is categorized as explanatory in nature. The researchers applied a purposive sampling technique with a sample of 100 respondents, while the data analysis was conducted using SPSS 26 to test the study hypotheses. The findings reveal that platform innovation significantly enhances muzaki decisions to contribute to zakat via digital platforms such as BAZNAS Platform, E-Commerce, and Fintech Services, while transparency also exerts a substantial positive influence on their decisions. Taken together, platform innovation and transparency are shown to have a strong and meaningful impact on muzaki decisions to contribute zakat through digital platforms. (BAZNAS Platform, E-Commerce, and Fintech Services).